Corporate Governance and Risk Management: A Case of Nepalese Commercial Banks - Kushwaha, Aashish; Kunwar, Ajay; Shah, Anuradha Kumari; Chhertri, Aarti Thapa; Mishra, Ashmita; Kapri, Asmita (Nepalese Journal of Business, 2025)
The study examines the impact of corporate governance and risk management in the context of Nepalese commercial banks. Non-performing loan and capital adequacy ratio are the dependent variables. The selected independent variables are board size, board diversity, audit committee, firm size, proportion of independent directors and board meeting. The study is based on secondary data of 12 commercial banks with 120 observations for the study period from 2013/14 to 2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB), Ministry of Finance (MoF) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance and risk management in the context of Nepalese commercial banks. The study showed that board size has a negative relationship with non-performing loan. It means that increase in board size leads to decrease in non-performing loan. Similarly, board diversity has a negative relationship with non-performing loan. It means that increase in board diversity, leads to decrease in non-performing loan. Further, proportion of independent directors have a negative relationship with non-performing loan. It means that increase in proportion of independent directors leads to decrease in non-performing loan. Moreover, board meeting have a negative relationship with non-performing loan. It means that increase in board meeting leads to decrease in non-performing loan. Similarly, the results show that audit committee has a negative relationship with non-performing loan and capital adequacy ratio indicating that increase in audit committee leads to decrease in non performing loan and capital adequacy ratio. Further, board size have a positive relationship with capital adequacy ratio. It means that increase in board size leads to increase in capital adequacy ratio. However, board diversity have a positive relationship with capital adequacy ratio. It means that increase in board diversity leads to increase in capital adequacy ratio. In addition, firm size have a positive relationship with capital adequacy ratio. It means that increase in firm size leads to increase in capital adequacy ratio.